การถ่ายยีนและวิเคราะห์การแสดงออกของยีน OsB2 ที่ควบคุมการสังเคราะห์แอนโทไซยานินในข้าว - ณ ราชสีมา, ลลิตา; คำโมนะ, กนกภรณ์; พงษ์เจริญกิต, แสงทอง; แสงทอง, วราภรณ์; เข็มกลัดเงิน, นฤมล; สกูลสิงหาโรจน์, ช่อทิพา; ชาวโพงพาง, ศรีเมฆ (Thai Journal of Science and Technology, 2019)
Abstract Anthocyanins are important antioxidants found in black pericarp rice. The OsB2 gene encodes a transcription factor which can activate anthocyanin biosynthesis in rice. In this study, transformation of Kasalath variety (red pericarp rice) using OsB2 cloned from a black pericarp rice via Agrobacterium was investigated for functional study on anthocyanin biosynthesis in rice. Fifty-nine transformants were regenerated and PCR analysis showed that 84.28 % carried the OsB2 transgene. The phenotypic traits of transgenic rice were similar to those of wild-type but developing and mature seeds showed purple pigmentation on their pericarp. Segregation analysis of gus genes showed the 3 : 1 ratio in T1 generation, indicating a single gene insertion in the rice genome. Phenotypic traits of T1 progeny were similar to those of the T0 transgenic rice plants. Semi-quantitative RT-PCR analysis revealed that overexpression of OsB2 gene in seedlings was found in T1 plants. In addition, seeds of T1 transgenic rice contained higher antioxidant activity than that of the untransformed plants. Keywords: Oryza sativa; OsB2; transformation; anthocyanin